HDAC6 inhibitor, ACY1215 suppress the proliferation and induce apoptosis of gallbladder cancer cells and increased the chemotherapy effect of gemcitabine and oxaliplatin. Issue 4 (11th January 2021) - Ruan, Yi; Wang, Luoluo; Lu, Yeting
Abstract: As an anti‐tumor agent, histone deacetylases (HDACs) inhibitors have attracted wide attention. ACY1215 is a highly effective selective inhibitor of HDAC6, which can inhibit many kinds of tumors. Whether the expression of HDAC6 and its new inhibitor ACY1215 can inhibit the proliferation of gallbladder cancer cells and induce their apoptosis remains to be further studied. The purpose of this study was to explore the effects of ACY1215 on the gallbladder cancer cells. Cell proliferation of GBC‐SD and SGC‐996 was assessed by cell counting kit‐8 assay and colony formation assay. Flow cytometry was used to detect the apoptosis of gallbladder cancer cells. Western blot was used to detect the expressions of PCNA，KI67, and apoptosis‐related proteins of gallbladder cancer cells. The HDAC6 inhibitor ACY1215 suppressed the proliferation of GBC‐SD and SDC‐996 cells and promoted the apoptosis of gallbladder cancer cells. The HDAC6 inhibitor ACY1215 increases the chemotherapy effect of gemcitabine and oxaliplatin. ACY1215 could suppress cell proliferation and induce apoptosis of GBC‐SD and SGC‐996, and increased the chemotherapy effect of gemcitabine and oxaliplatin, which provides a rationale for the combination of HDAC6 selective inhibitors with other anticancer agents in treating gallbladder cancer.